Tafsir Al-Misbah as a Pedagogical Framework for Qur’anic Character Education in Islamic Boarding Schools - Kafrawi; Sulthan Al Aziz (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2025)
This study examines how Tafsir Al Misbah by M. Quraish Shihab can function as a coherent pedagogical framework for Qur’anic character education in Islamic boarding schools. Existing research has largely focused on identifying Qur’anic values within tafsir texts, yet has not explained the pedagogical mechanisms through which these values are internalized by students. Addressing this gap, the study investigates how tafsir is integrated into curricular, non curricular, and cultural practices in two pesantren with different institutional orientations. A qualitative multiple case study design was employed. Data were collected through in-depth interviews, participatory observations, and documentation of tafsir-based learning activities. The data were analyzed using thematic coding and cross case comparison following Miles, Huberman, and Saldaña’s interactive model. The findings show three key results. First, Tafsir Al Misbah is integrated through a structured three-dimensional model that includes reflective and project-based learning in the curriculum, value habituation through halaqah and muhasabah, and institutional culture building through symbolic Qur’anic practices. Second, this integration consistently cultivates core Qur’anic character values such as honesty, patience, responsibility, social empathy, and sincerity. Third, teachers play a central role as moral exemplars and reflective facilitators who translate tafsir into lived practices. These findings imply that tafsir can operate not only as a source of religious knowledge but also as a pedagogical system that links interpretation, reflection, and behavioral transformation. The study concludes by recommending the adoption of the three-dimensional integration model to strengthen character education in pesantren and other faith-based institutions. ABSTRAK Penelitian ini mengkaji bagaimana Tafsir Al Misbah karya M. Quraish Shihab dapat berfungsi sebagai kerangka pedagogis yang koheren bagi pendidikan karakter Qur’ani di pesantren. Studi sebelumnya umumnya berfokus pada identifikasi nilai Qur’ani dalam teks tafsir, tetapi belum menjelaskan mekanisme pedagogis yang memungkinkan nilai tersebut terinternalisasi dalam diri santri. Untuk mengisi kesenjangan ini, penelitian ini menganalisis bagaimana tafsir diintegrasikan ke dalam praktik kurikuler, non kurikuler, dan kultural pada dua pesantren dengan orientasi institusional yang berbeda. Penelitian ini menggunakan desain studi kasus ganda dengan pendekatan kualitatif. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan dokumentasi aktivitas pembelajaran berbasis tafsir. Analisis data dilakukan melalui pengodean tematik dan perbandingan lintas kasus menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan tiga temuan utama. Pertama, Tafsir Al Misbah diintegrasikan melalui model tiga dimensi yang mencakup pembelajaran reflektif dan berbasis proyek dalam kurikulum, pembiasaan nilai melalui halaqah dan muhasabah, serta pembentukan budaya institusional melalui praktik simbolik Qur’ani. Kedua, integrasi ini secara konsisten menumbuhkan nilai karakter Qur’ani seperti kejujuran, kesabaran, tanggung jawab, empati sosial, dan keikhlasan. Ketiga, guru berperan sentral sebagai teladan moral dan fasilitator refleksi yang menerjemahkan tafsir menjadi praktik kehidupan sehari hari. Temuan ini menunjukkan bahwa tafsir dapat berfungsi tidak hanya sebagai sumber pengetahuan keagamaan, tetapi juga sebagai sistem pedagogis yang menghubungkan penafsiran, refleksi, dan transformasi perilaku. Penelitian ini merekomendasikan penerapan model integrasi tiga dimensi untuk memperkuat pendidikan karakter di pesantren dan lembaga pendidikan berbasis agama lainnya.